Dregea cuneifolia Tsiang & P. T. Li - a new record for flora of Vietnam - Bach, Tran The (Academia Journal of Biology, 2012)
The genus Dregea comprises approximately 12 species and is distributed in Asia, Africa. In Vietnam, a species of Dregea has been recognized (Pham Hoang Ho, 1993, 2000; Tran The Bach, 2005): Dregea volubilis (L. f.) Benth. & Hook.. We have confirmed the distribution of Dregea cuneifolia Tsiang & P. T. Li in Vietnam. The species is found in Lam Dong province (Da Lat), the specimens are preserved in HN herbarium - Institute of Ecology and Biological Resources. Therefore, the genus Dregea with 2 species has been recognized in Vietnam. In Vietnam, genus Dregea is distinguished from other genera of Asclepiadaceae by characters of pollinarium, corolla and corona. Some main characters of D. cuneifolia: Lianas. Leaf blade oblong. Corolla greenish white, ca. 9 mm in diam.; tube ca. 2 mm, glabrous; lobes ovate-triangular, ca. 4 ´ 4 mm, margin ciliate. Corona lobes globose. Pollinia spatulate, 0.6 ´ 0.16 mm; caudicles 0.13 mm; corpusculum 0.45 mm. Ovaries glabrous, ca. l mm. Loc. class.: China: Guangxi: Damiao Shan, bushland, 500-800 m, 7 Sept. 1958. Typus: S. H. Chun 15587 (HT: SCBI). Ecology and Biology: Flowering april-september. In bushland, light place. Distribution: Lam Dong province (Da Lat). Also in China. Studied specimens: Lam Dong (Da Lat), 12/04/84, LX-VN 1470 (HN). Dregea cuneifolia is distinguished from Dregea volubilis by some characters: Dregea cuneifolia: Leave oblong. Pollinium 0.6 mm. Ovaries glabrous; Dregea volubilis: Leave broad ovate or cordate. Pollinium < 0.5 mm. Ovaries pubescent.